Perancangan Sistem Pencarian File Dokumen Dengan Agen Bergerak Metode Branching Pada Sistem Terdistribusi - muhammad hasbi (Jurnal Ilmiah SINUS, 2010)
Existence of the file documents in an agency is required by the leadership. The position of the file can be spread over several units (sections) in the agency, requiring the search process to determine the existence of the file. Search process is performed using mobile agent that is aglet. Aglet can move to form a 'slave' aglet according to its function as work aglet to search the files in the units with Branching. Designing a search system files on distributed systems using the aglet has been created to produce an analysis aglet role in the search process in a distributed system.Keywords : Search, mobile agent, aglet, distributed, branching